National Culture of India - Husain,S. Abid (New Delhi, 2003)
This book is a learned exposition of the theory that, amidst the great diversity in every walk of life in India. there exists an underlying unity. To elucidate thesis the author has made a chronological survey of Indian history and the movements that have shaped the country. He has concluded by enumerating the various fissiparous tendencies present today, but still sees hope for the future.
Keywords: Culture-India